Intravenous tenecteplase compared with alteplase for acute ischaemic stroke in Canada (AcT): a pragmatic, multicentre, open-label, registry-linked, randomised, controlled, non-inferiority trial. Issue 10347 (16th July 2022) - Menon, Bijoy K; Buck, Brian H; Singh, Nishita; Deschaintre, Yan; Almekhlafi, Mohammed A; Coutts, Shelagh B; Thirunavukkarasu, Sibi; Khosravani, Houman; Appireddy, Ramana; Moreau, Francois; Gubitz, Gord; Tkach, Aleksander; et al.
Summary: Background: Intravenous thrombolysis with alteplase bolus followed by infusion is a global standard of care for patients with acute ischaemic stroke. We aimed to determine whether tenecteplase given as a single bolus might increase reperfusion compared with this standard of care. Methods: In this multicentre, open-label, parallel-group, registry-linked, randomised, controlled trial (AcT), patients were enrolled from 22 primary and comprehensive stroke centres across Canada. Patients were eligible for inclusion if they were aged 18 years or older, with a diagnosis of ischaemic stroke causing disabling neurological deficit, presenting within 4·5 h of symptom onset, and eligible for thrombolysis per Canadian guidelines. Eligible patients were randomly assigned (1:1), using a previously validated minimal sufficient balance algorithm to balance allocation by site and a secure real-time web-based server, to either intravenous tenecteplase (0·25 mg/kg to a maximum of 25 mg) or alteplase (0·9 mg/kg to a maximum of 90mg; 0·09 mg/kg as a bolus and then a 60 min infusion of the remaining 0·81 mg/kg). The primary outcome was the proportion of patients who had a modified Rankin Scale (mRS) score of 0–1 at 90–120 days after treatment, assessed via blinded review in the intention-to-treat (ITT) population (ie, all patients randomly assigned to treatment who did not withdraw consent). Non-inferiority was met if the lower 95% CI of the difference in the proportion of patients who met the primary outcome between the tenecteplase and alteplase groups was more than –5%. Safety was assessed in all patients who received any of either thrombolytic agent and who were reported as treated. The trial is registered with ClinicalTrials.gov, NCT03889249, and is closed to accrual. Findings: Between Dec 10, 2019, and Jan 25, 2022, 1600 patients were enrolled and randomly assigned to tenecteplase (n=816) or alteplase (n=784), of whom 1577 were included in the ITT population (n=806 tenecteplase; n=771 alteplase). The median age was 74 years (IQR 63–83), 755 (47·9%) of 1577 patients were female and 822 (52·1%) were male. As of data cutoff (Jan 21, 2022), 296 (36·9%) of 802 patients in the tenecteplase group and 266 (34·8%) of 765 in the alteplase group had an mRS score of 0–1 at 90–120 days (unadjusted risk difference 2·1% [95% CI – 2·6 to 6·9], meeting the prespecified non-inferiority threshold). In safety analyses, 27 (3·4%) of 800 patients in the tenecteplase group and 24 (3·2%) of 763 in the alteplase group had 24 h symptomatic intracerebral haemorrhage and 122 (15·3%) of 796 and 117 (15·4%) of 763 died within 90 days of starting treatment Interpretation: Intravenous tenecteplase (0·25 mg/kg) is a reasonable alternative to alteplase for all patients presenting with acute ischaemic stroke who meet standard criteria for thrombolysis. Funding: Canadian Institutes of Health Research, Alberta Strategy for Patient Oriented Research Support Unit.